CEREBRAL CIRCULATION AND LAWS OF HEMODYNAMICS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Arterial system - blood supply to the brain. Microcirculation - blood circulation at the capillary level. Hemoencephalic barrier (HEB) - a protective filter for the brain. Mechanisms of cerebral circulation regulation.Arterial tizim (Miyani qon bilan ta’minlash)